Ligand promoted and controlled palladium-catalyzed intramolecular Heck reaction of homoallyl alcohols: a facile synthesis of cyclopentaannulated quinolines - Singh, Radhey M.; Chandra, Atish; Sharma, Neha; Singh, Bhawana; Kumar, Ritush (Tetrahedron, 2012)
Bidentate phosphine ligands in palladium-catalyzed intramolecular Heck reactions of 2-chloroquinolin-3-yl-(1-homoallyl)alcohols are described to afford facile synthesis of 3-methylene-2,3-dihydro-1H-cy-clopenta[b]quinolines in improved yields. We further observed using bulky aromatic phosphine ligand in Pd-catalyzed intermolecular Heck coupling reaction at olefinic centers with iodobenzene also favored exclusively Heck products in excellent yield. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Heck cyclization; Homoallyl alcohol; Ligand promoted; Palladium-catalyzed; Quinoline